What drives idiosyncratic volatility over time? - Sousa, Sónia R. (2018)
We document the patterns of market-wide and firm-specific volatility in the Portuguese stock market over the 1991–2005 period and test several explanations for the behavior of firm-level idiosyncratic volatility. Unlike previous studies we find no evidence of a statistically significant rise in firm- specific volatility. On the contrary, the ratio of firm-specific risk to total risk slightly decreases. We show that this result stems from new listings of large privatized companies that display lower firm-specific risk. Our findings are consistent with the idea that changes in idiosyncratic volatility are related to changes in the composition of the market.